Child - parent agreement on reports of disease, injury and pain - Saartok Tönu; Sundblad Gunilla; Engström Lars-Magnus T (BMC, 2006)
Abstract Background Studies on school students are indicating that somatic complaints and pain have increased during the past decades. Throughout this period there has been a change in methodology from proxy reports by parents to having the students themselves act as the respondents, possible explaining some of the increase in prevalence. The aim of this study was to compare the agreement of answers from students with answers given by their parents regarding the students' medical background and subjective rating of perceived health with specific focus on frequency of headache, musculoskeletal pain and tiredness. Methods The participating students came from eleven different schools in Sweden. The schools were a sub sample of randomly selected schools originally participating in a larger multidisciplinary base study. Those 8th grade students present at school on the test date became the subjects of the investigation. A total of 232 students answered, assisted by the test leader, a specially designed self-complete questionnaire at school. Their parents were, at the same time, contacted and 200 answered a similar mailed-out questionnaire. One hundred and eighty-six (186) corresponding student-same parent questionnaires were registered for which comparisons of answers could be made and analysis conducted. Results When a child is in good health, in absence of diseases, pain and injuries, his or her assessment matches up with their parent. Children and parents also showed agreement in cases of severe injuries and frequent (daily) complaints of knee pain. Less frequent headaches, back- and musculoskeletal pain and other complaints of minor injuries and less wellbeing, such as students' tiredness, were all under-reported and under-rated by their parents. Conclusion When assessing the perceived health and wellbeing of students, their own expressions should be the basis for the data collection and analysis rather than relying entirely on parental reports.